Peran Guru Pendidikan Agama Islam dalam Menghadapi Permasalahan Pembelajaran Fiqih di Sekolah Umum - Sri Rahmawati (Jurnal Pendidikan Dasar Islam, 2023)
The aim of this research is to describe the role of Islamic Religious Education teachers in dealing with the problems of learning fiqh in public schools. This research uses a qualitative approach with the library research method. The findings of this research are that problems in learning fiqh have several problem points related to the beliefs of a group, which gives rise to denigration of other groups. Claiming that his group is right and others are wrong. The lack of knowledge of teachers who explain or teach is very minimal regarding this fiqh. So that students cannot understand it well and it creates an indifferent attitude so they don't want to care about the fiqh learning delivered by the teacher. Most of the teacher's knowledge is only general knowledge and not detailed knowledge regarding this fiqh subject. Of course, this hinders the progress of fiqh lessons, both for teachers and students. If the teacher who teaches fiqh has minimal knowledge, it will be difficult for students to understand this lesson.